Design optimization of a high-speed synchronous reluctance machine - Di Nardo, Mauro; Lo Calzo, Giovanni; Galea, Michael; Gerada, C. (IEEE, 2018)
Synchronous reluctance machines, including the per¬manent magnet assisted variants are competitive motor topologies if the application requires high efficiency and a cost effective solution with a high flux weakening capability. However, increas¬ing operating speeds incur challenging design and development decisions, mainly in order to find design solutions that ensure the machines structural integrity without compromising the overall performance. In this paper, a comprehensive design procedure for high speed synchronous reluctance machines is presented. In order to validate the procedure, a 5 kW, 80000 rpm machine is considered. The proposed strategy consists of a two-step procedure in which the electromagnetic and structural designs have been properly decoupled dividing the design space in two subsets. Each subset mainly affects the electromagnetic or the structural performances. Several structural design optimizations have been then performed with the aim of finding the optimal trade-off between the rotor geometrical complexity (that defines the required computational resources) and the electromagnetic performance. The reported experimental tests of the prototyped machine validate the proposed design strategy which can be used as general guidelines on the structural design of synchronous reluctance machines.